PERFORMANCE ASSESSMENT OF THE BALKAN COUNTRIES IN THE INFORMATION AND COMMUNICATION TECHNOLOGIES SECTOR - Radivojevic, Vladimir; Krstić, Bojan; Stanojević, Jelena (Annals of Spiru Haret University. Economic Series, 2021)
The rapid technological development of the last decades has affected practically all areas of the economy, society, and culture. Almost every aspect of life and work in the modern world to a greater or lesser extent depend on the use of information and communication technologies (ICT). The aim of this paper is to analize the ICT performance of ten Balkan countries and to highlight areas that need further improvement. The analysis is based on the data published by the International Telecommunication Union in annual Measuring the Information Society Report. The research is conducted through comparative analysis and benchmarking method. The ten best-positioned European countries in terms of ICT development represent the benchmark group. The analysis finds low level of national ICT performance of the Balkan countries compared to the selected European countries. The conclusions of this research may serve as guidelines for ICT policy makers in the observed economies.